PARTISIPASI MASYARAKAT PADA PERENCANAAN PEMBANGUNAN DI DESA IGO KECAMATAN LOLODA UTARA KABUPATEN HALMAHERA UTARA - SIBU, SUSI YURLIAN; PANGKEY, MASJE SILIJA; RURU, JOORIE MARHAEN (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract : The background of this study is that each village has difficulties or obstacles to be solved in order to achievecommon goals. The constraints occur in various participation and the field of development planning, whether or notachieved the development of the quality of existing human resources. Therefore, the researcher focused on CommunityParticipation in Development Planning in Igo Village, North Loloda Sub-district, North Halmahera District. The problemsin this research are how the community participation, the efforts made and the results achieved in improving participationbased on development planning in Igo Village. This research is a study of qualitative descriptions by taking the backgroundof Igo Village. The purpose of this study was to decrypt the community participation in Igo Village. The data collection isdone by observation, interview, and documentation. Data analysis is done by data collection, data reduction, datapresentation then drawn conclusion.The results of research using participatory methods in development planning in Igo Village begins with thegovernment conveying the goals of development planning and motivating the community, presenting information,evaluating community participation. While the results of community participation in Igo Village experience a lack ofimprovement, this can be proven by the final evaluation of development planning that is in the category less than themaximum because the community is less participate in development planning. The improvement of the final evaluationresult on community participation is inseparable from the role of the government that continues to invite, motivate, thecommunity to participate in the development planning that the village or village government is proposing to the village.Keywords: Participation, Planning, Development